Clinical Manifestations of Runny nose among Patients Attending Baqubah Teaching Hospital - Jaafar Khalaf, Qays; Lafta Salman, Ali; Abdelmajid Al katatbeh, Mohammad; Nabhan Hussein, Sura (Diyala Journal of Medicine, 2024)
Background: The runny nose refers to a discharge (fluid) coming from the nasal passages.Runny nose is associated with inflammation and swelling (congestion) of the inner lining of the nasal passages and sinuses. May associated with atopic condition the patient complain from nasal obstruction, runny nose, episode of sneezing, and nasal pruritis. Objective: To examine the demographic distribution, clinical features, and age disparities among male and female patients with Runny nose (Rhinorrhea). Patients and Methods: A study was done on 100 AR patients at Baqubah Teaching Hospital. Information on demographics, clinical symptoms, and age variations between males and females were gathered and examined through the use of descriptive statistics and independent sample t-tests. Results: The Findings revealed that most of the subjects were women (56%) and homemakers (38%), with an average age of 29.73 years. Frequent symptoms comprised of sneezing (93%), runny nose (83%), itchy nose (74%), and stuffy nose (92%). There was no notable variation in age between males and females (p = 0.139). Conclusion: Clinical symptoms of runny nose are often recognized consist of rhinorrhea, sneezing, obstruction of the nasal passages with lacrimation and pruritus of the nasal mucosa, conjunctiva and oropharynx with history of allergic rhinitis. Conditions commonly associated with allergic rhinitis include asthma, sinusitis, allergic conjunctivitis and atopic dermatitis. Long standing disease can lead to mucosa remodeling, atrophic skin changes, nasal infection and overall increased morbidity.